2004
DOI: 10.1037/0022-3514.86.4.560
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Universals of Mate Poaching Across 53 Nations: The Effects of Sex, Culture, and Personality on Romantically Attracting Another Person's Partner.

Abstract: and 121 Members of the International Sexuality Description Project As part of the International Sexuality Description Project, 16,954 participants from 53 nations were administered an anonymous survey about experiences with romantic attraction. Mate poachingromantically attracting someone who is already in a relationship-was most common in Southern Europe, South America, Western Europe, and Eastern Europe and was relatively infrequent in Africa, South/Southeast Asia, and East Asia. Evolutionary and social-role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
138
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(153 citation statements)
references
References 69 publications
(171 reference statements)
11
138
1
3
Order By: Relevance
“…That is, seekers of long-term relationships are presumably less likely to act as competitors by mate-poaching a current or future partner, and thus can be viewed more favorably compared with those who seek short-term relationships. As part of the International Sexuality Description Project, SCHMITT et al (2004) found that, in North America, 62% of men and 40% of women self-report that they have been tempted to poach someone else's mate for a short-term sexual relationship. In contrast, approximately 20% of long-term relationships begin when one or both individuals are already involved with other people.…”
Section: Discussionmentioning
confidence: 99%
“…That is, seekers of long-term relationships are presumably less likely to act as competitors by mate-poaching a current or future partner, and thus can be viewed more favorably compared with those who seek short-term relationships. As part of the International Sexuality Description Project, SCHMITT et al (2004) found that, in North America, 62% of men and 40% of women self-report that they have been tempted to poach someone else's mate for a short-term sexual relationship. In contrast, approximately 20% of long-term relationships begin when one or both individuals are already involved with other people.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies with couples could use some of the items presented here as the basis for the creation of a validated scale. Also, future questionnaire studies of a slightly different format to the present one could perhaps employ more objective measures such as number of extra-pair copulations (EPCs) obtained over the course of various relationships, number of dates, telephone numbers secured and mate poaching attempts (Schmitt, 2004;Schmitt & Buss, 2001;Parker & Burkley, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, additional research should be conducted with more diverse samples. Schmitt (2004) report that mate poaching is a universal mating strategy. However, Schmitt (2004) did not investigate tactics used for short-term mate poaching.…”
Section: Limitations and Future Directionmentioning
confidence: 99%
“…Davies, Shackelford, and Hass (2007) discovered that about 30% of college aged men and women reported have tried to mate poach. A cross-cultural investigation conducted by the International Sexuality Description Project, using data from 53 nations, researchers representing six continents, 13 islands, and 28 languages, found that mate poaching exists throughout several societies (Schmitt, 2004).…”
Section: Mate Poachingmentioning
confidence: 99%